Integrating Islamic Economic Principles into Green Campus Implementation: Empirical Evidence from Indonesia Universities - Eliza, Any; Rifan, Dinda Fali; Ningsih, Nur Wahyu; Susanto, Is (El-Usrah: Jurnal Hukum Keluarga, 2025)
This study aims to describe the implementation of green campus initiatives at universities in Indonesia, with particular emphasis on how islamic economic principles can further support environmental sustainability. Using the national level UI GreenMetric World University Rankings in the category of Most Sustainable University, three universities were selected as researh samples. This field research employed interviews and documentation from sustainability reports and official university websites. The implementation of the green campus was measured using four key instruments: Environmental Awareness, Environmental Involvement, Environmental Reporting, and Environmental Auditing. The findings indicate that all three universities have implemented the stages of environmental awareness, involvement, and reporting, but have not fully implemented environmental auditing. Participation in the UI GreenMetric reflects increasing awareness of sustainability issues among universities and their surrounding communities. Notably, University X demonstrated the highest level of implementation across the four green campus indicators. Futhermore, islamic economic principles such as moderation (wasatiyyah), stewardship (khalifah), and social responsibility (maslahah) offer an ethical and moral foundation to strengthen sustainability efforts in islamic universities. These principles promote the responsible use of resources, discourage wastefulness (israf), and encourage equity in resource management. Legitimacy theory supports the notion that organizations must align with societal and environmental value systems, as greater responsibility towards the environment enhances their reputation and public trust. Therefore, integrating islamic economic values into green campus initiatives not only aligns with global sustainability practices but also positions universities as ethical leaders in promoting environmental consciousness